Can posttraumatic growth after breast cancer promote positive coping?—A cross‐lagged study. Issue 4 (14th February 2019) - Hamama‐Raz, Yaira; Pat‐Horenczyk, Ruth; Roziner, Ilan; Perry, Shlomit; Stemmer, Salomon M.
Abstract: Objectives: The diagnosis of breast cancer can be associated with significant emotional distress, yet, over time, cancer survivors also may experience positive psychological changes labeled posttraumatic growth (PTG). Two alternative paths between coping strategies and PTG were tested among breast cancer patients, employing longitudinal design: Would PTG after medical treatment of breast cancer lead to an increase in reporting positive coping strategies; alternatively, would positive coping strategies after medical treatment of breast cancer lead to increased PTG. Methods: A longitudinal study was conducted among 198 breast cancer patients who completed validated self‐report scales, at five time points: at 3 months after completing active medical treatment (T1); after 6 months (T2); after 1 year (T3); after 2 years (T4); and after 7 years (T5). The current study analyzes three time points: T1, T3, and T5 using structural equation modeling. Results: Our results support the path that describes the first alternative, that higher report of PTG after medical treatment of breast cancer patients would lead to increased report of positive coping strategies. In addition, positive coping strategies were found to be positively linked to PTG after 6 months, and the link was slightly stronger after 2 years. Nevertheless, 7 years after diagnosis, no association was found between positive coping strategies and PTG measurements. Conclusions: Finding positive meaning after coping with breast cancer, as reflected in PTG, may be a significant resource in coping with cancer, and it may lead to increase of positive coping strategies.